Usefulness of 2D-Perfusion Analysis for the Assessment of Unilateral Cervical Internal Carotid Artery Stenosis - Akifumi Yoshikawa; Takehiro Uno; Iku Nambu; Tomoya Kamide; Kouichi Misaki; Mitsutoshi Nakada (JNET, 2021)
Objective: We investigated the usefulness of 2D-perfusion analysis for the evaluation of cerebral blood flow in unilateral cervical internal carotid artery stenosis. Methods: We conducted a 2D-perfusion analysis during cerebral angiography and 123I-iodoamphetamine (IMP) single photon emission computed tomography (SPECT) for unilateral cervical internal carotid artery stenosis without contralateral stenosis. The relationship between the ratio of the lesion side to the normal side in the parameters obtained by 2D-perfusion and the value calculated by stereotactic extraction estimation (SEE) analysis of SPECT was statistically examined.Results: The ratios of the lesion side to the normal side regarding the peak arrival time (AT; time to peak [TTP]) of the contrast agent and the mean filling time (mean transit time [MTT]) of the contrast agent in 2D-perfusion significantly correlated with the area of Stage II and increase ratio (I.R) ≤30% in the SEE analysis (p = 0.002, 0.003). Conclusion: 2D-perfusion analysis can be used to estimate the extent of impaired cerebrovascular reserve (CVR) area in unilateral internal carotid artery stenosis.